Microvesicles Derived from Indoxyl Sulfate Treated Endothelial Cells Induce Endothelial Progenitor Cells Dysfunction - Carmona, Andres; Guerrero, Fatima; Buendia, Paula; Obrero, Teresa; Aljama, Pedro; Carracedo, Julia (Frontiers in Physiology, 2017)
Cardiovascular disease is a major cause of mortality in chronic kidney disease patients. Indoxyl sulfate (IS) is a typical protein-bound uremic toxin that cannot be effectively cleared by conventional dialysis. Increased IS is associated with the progression of chronic kidney disease and development of cardiovascular disease. After endothelial activation by IS, cells release endothelial microvesicles (EMV) that can induce endothelial dysfunction. We developed an in vitro model of endothelial damage mediated by IS to evaluate the functional effect of EMV on the endothelial repair process developed by endothelial progenitor cells (EPCs). EMV derived from IS-treated endothelial cells were isolated by ultracentrifugation and characterized for miRNAs content. The effects of EMV on healthy EPCs in culture were studied. We observed that IS activates endothelial cells and the generated microvesicles (IsEMV) can modulate the classic endothelial roles of progenitor cells as colony forming units and form new vessels in vitro. Moreover, 23 miRNAs were contained in IsEMV including four (miR-181a-5p, miR-4454, miR-150-5p, and hsa-let-7i-5p) that were upregulated in IsEMV compared with control endothelial microvesicles. Other authors have found that miR-181a-5p, miR-4454, and miR-150-5p are involved in promoting inflammation, apoptosis, and cellular senescence. Interestingly, we observed an increase in NFκB and p53, and a decrease in IκBα in EPCs treated with IsEMV. Our data suggest that IS is capable of inducing endothelial vesiculation with different membrane characteristics, miRNAs and other molecules, which makes maintaining of vascular homeostasis of EPCs not fully functional. These specific characteristics of EMV could be used as novel biomarkers for diagnosis and prognosis of vascular disease.